Municipal Reform on the Island of Montreal: Tensions Between Two Majority Groups in a Multicultural City - Sébastien Arcand; Danielle Juteau; Sirma Bilge; Francine Lemire (Fondazione Eni Enrico Mattei (FEEM), 2003)
For several years now, many cities across the world have undergone, for administrative and political reasons, mergers that have considerably reduced the number of municipalities on a given territory. This tendency affects various urban contexts, as evidenced by recent mergers in Toronto, Ottawa and Halifax (Canada), Baltimore (United States), and in other countries such as Scotland, Australia and England. Quebec has not escaped this trend, and since January 1st 2002, six major urban areas were created. While mergers now constitute a familiar occurrence, the processes they entail differ considerably from site to site, questioning existing power structures, administrative procedures, and modes of belonging. In Quebec, the case of Montreal stands out, because of its strategic economic position, and also because of the historical and often conflictual relations between its diverse ethnic and linguistic collectivities. This paper examines how the merger of twenty-nine municipalities on the island of Montreal into a single city now composed of twenty-seven boroughs, modifies the relations between the two dominant majorities and, more specifically, the capacity of English Canadians to control their institutions and daily affairs. Does this transformation, which involves the disappearance of municipalities, some of which were governed by English Canadians and other Anglophones, follow the trend observed in Quebec since the sixties, involving a loss in the latter's institutional completeness, organizational capacity, and spheres of autonomy?
Keywords: Z10; 330; Municipal Reform; Conflict; Tension; Multiculturalism